Karakteristik mineralisasi epitermal di Daerah Taran, Hulu Kahayan, Kalimantan Tengah berdasarkan studi mikroskopis, X-Ray Diffraction (XRD), dan inklusi fluida - Danny Zulkifli Herman (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no3.20064Taran area is occupied predominantly by piroclastic rocks and locally intercalations of lenticular claystones and sandstones. The pyroclastic rocks are intruded by diorite, dacite and andesite, leading alteration and mineralization within the host rocks. Mineralization occurs as a vein type and is associated with a number of pervasive alteration types named respectively: quartz-illite- montmorillonite-kaolinite ± pyrite, quartz-illite ± pyrite, quartz-illite-chlorite ± pyrite and quartz- kaolinite-illite ± pyrite. On the other hand, a propylitic alteration also occurs within the andesite intrusion composed of calcite-epidote-chlorite-sericite-quartz ± pyrite. The mineralization is characterized by several zones of quartz stockwork containing gold and associated ore minerals of chalcopyrite, sphalerite, galena, pyrite and argentite. The quartz veins occurs as fi llings of structural openings in the form of milky quartz and amethyst with textures of sugary, comb, and dogteeth. Evaluation work on results of microscopic (petrography and mineragraphy), X-Ray Diffraction (XRD), and fl uid inclusion studies, and chemical analysis of entirely altered rock/quartz vein samples shows that the alteration and mineralization process were closely related to a change of hydrothermal fl uids, from near neutral into acid conditions at a temperature range of >290o – 100oC. The appearances of quartz variation indicate a relationship with repeated episodes of boiling in an epithermal system, as ground water mixed with hot vapor originated from a remained post-magmatic solution. Corresponding to a salinity of average 1,388 equiv.wt.% NaCl, it indicates that the ore minerals bearing quartz veins were deposited at a depth range of 640 – 1020 m beneath paleosurface.